FACTORS ASSOCIATED WITH FEAR OF CHILDBIRTH AMONG PREGNANT WOMEN - Dewi Marfuah; Shindy Kartika Sari; Astri Mutiar; Dewi Srinatania (DPW PPNI Provinsi Jawa Barat, 2025)
Background: Fear of Childbirth (FoC) is a common psychological concern during pregnancy and may negatively affect maternal health and birth outcomes, including increased blood pressure, prolonged labor, and postpartum depression. FoC is influenced by various demographic, obstetric, and psychosocial factors. Objective: This study aimed to identify factors associated with FoC among pregnant women. Methods: A quantitative cross-sectional study was conducted involving 113 pregnant women across the first to third trimesters. FoC was assessed using the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ), while perceived social support was measured using the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using Pearson correlation, Spearman correlation, and multiple linear regression analyses. Results: Bivariate analysis demonstrated that maternal age, household income, and parity status were significantly associated with FoC (p < 0.05). In contrast, education level, occupation, gestational age, and perceived social support showed no significant associations (p > 0.05). Multivariate analysis revealed that parity status was the most influential factor affecting FoC among pregnant women. Conclusion: Younger women and those with lower parity are more likely to experience FoC, primarily due to limited childbirth experience and uncertainty about labor and infant care. Higher household income was also associated with greater FoC, possibly related to increased exposure to childbirth-related information. Strengthening antenatal education and psychological support is essential to enhance maternal preparedness for childbirth.